2020
DOI: 10.1002/bjs5.50240
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of reporting benefits and harms of surgical interventions in randomized clinical trials

Abstract: Background Standardized reporting methods facilitate comparisons between studies. Reporting of data on benefits and harms of treatments in surgical RCTs should support clinical decision‐making. Correct and complete reporting of the outcomes of clinical trials is mandatory to appreciate available evidence and to inform patients properly before asking informed consent. Methods RCTs published between January 2005 and January 2017 in 15 leading journals comparing a surgical treatment with any other treatment were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…According to CONSORT -A, advent events is an important piece of information for the reader and should be reported in abstracts (Stubenrouch et al, 2020). Our study found no abstracts report this information.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…According to CONSORT -A, advent events is an important piece of information for the reader and should be reported in abstracts (Stubenrouch et al, 2020). Our study found no abstracts report this information.…”
Section: Discussionmentioning
confidence: 62%
“…Overall, however, less than a quarter of the included abstracts adequately reported randomization methods. Reporting deficiencies in these items are also found in other areas (Seta et al, 2020;Stubenrouch et al, 2020). Since a lack of description of important methodological items could cause bias and affects the reliability and validity of RCT abstracts (Seta et al, 2020), we encourage trialists and journal editors to work towards solutions to mitigate these issue.…”
Section: Discussionmentioning
confidence: 97%
“…Systematic reviews also called for RCTs addressing the use of methylene blue. There were also gaps in data exploring laser depilation to prevent recurrence [ 20 , 21 ]. There was a clear need for further data exploring the roles of wound care adjuncts in the aftercare setting [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Systematic reviews call for: trials on laser hair depilation to prevent recurrence [ 20 , 21 ]…”
Section: Resultsmentioning
confidence: 99%
“…A potential barrier may stem from the general dearth of high-quality reporting of RCT data to facilitate clear communication of treatment outcomes with patients. 84 Despite the availability of guidelines such as the CONSORT statement, a review of a sample of RCTs published within the past two decades in leading surgical and medical journals found only 5 of 88 articles mentioned an NNT or NNH. However, an NNT/NNH could have been calculated based on the absolute figures given for 8 out of 46 reported primary outcomes (NNT) and 2 of the 63 documented primary adverse outcomes (NNH).…”
Section: Discussionmentioning
confidence: 99%